Exploring temporal trends and burden of traumatic shoulder dislocation: a global perspective - Chen, Cheng; Ye, Tianbao; Jiang, Jiantao; He, Wenbao; Xia, Jiang; Yang, Yunfeng (Frontiers in Public Health, 2024)
Objective: To explore the geographical and temporal trends of traumatic shoulder dislocation, describe the association between the social and demographic factors and the health burden due to traumatic shoulder dislocation, and further investigate its causes.Methods: Data on traumatic shoulder dislocation was collected from the Global Burden of Disease 2019, spanning the years 1990 to 2019. The epidemiology and disease burden were examined at global, regional, and national levels. Additionally, the age and gender patterns were analyzed, followed by an investigation into the primary causes.Lastly, the study studied the correlation between age-standardized rates and the Socio-Demographic Index (SDI).Results: Over a span of thirty years, both the crude and age-standardized rates of incidence and years lived with disability (YLDs) rates for all genders displayed a slight fluctuating downward trend. The incidence and YLDs rates in males were consistently higher than those in females. The study analyzed both incidence and YLDs rates of the global, regional, and national of traumatic shoulder dislocations from 1990 to 2019, as well as the temporal trends. Among males, the highest incidence rate was observed in young adulthood, while females exhibited the highest incidence rate in old age. This pattern was mirrored in the YLDs rate. Falls were identified as the main cause contributing to the disease burden related to traumatic shoulder dislocations. Moreover, a positive correlation was found between the age-standardized rates and SDI.The disease burden of traumatic shoulder dislocation has not significantly decreased from 1990 to 2019. The incidence and YLD rates are associated with age, gender, and SDI. A thorough examination of the disease burden contributes to the efficient allocation and utilization of resources, as well as the development of targeted and effective intervention strategies.